Visualisation on blood flow mechanism of vein in deep vein thrombosis (DVT) study - Aziz, Nur Shazilah (2018)
Blood velocity is expected to be a parameter for detecting blood abnormality, for example the existence of thrombus. Proper blood flow in veins are important to ensure the effective return of deoxygenated blood to the heart. It is challenging to determine the vessel condition, due to the inability to visualize the thrombus presence in the vessel. This is due to the noise that are present in the image obtained from Ultrasound scanning. Since it is difficult to recognize the vessel condition at the earliest stage of Deep Vein Thrombosis (DVT), this study aims to assess the velocity and vorticity at the valve region using the Computational Fluid Dynamics (CFD) method. The velocity ofblood and the size of valve orifice are considered important parameters in designing the vein. Following Virchow's triad theory, the stenosis and irregularities of velocity in the blood vessel are known as the risk factors for thrombus formation. This study also includes the effect of different sizes of valve orifice with the existence of 1 mm and 3 mm thrombus, as both represent the DVT condition. From the simulation, the velocity contour plot of the blood flow can be visualised clearly. The blood distribution was presented using velocity profile while the fluid particles movement was shown by velocity vector. Vorticity contour meanwhile provides information on the tendency of particles to move in circular motion. Based on the simulation, the low blood velocity clearly shows the low velocity region which resides at the cusps area and at the beginning of the valve leaflets. Therefore, the present study has successfully shown that the CFD method is able to determine and evaluate the probable location of thrombus development in the blood vessel.